ANTINUCLEAR ANTIBODIES IN PATIENTS WITH UNEXPLAINED RECURRENT ABORTIONS - Asaithambi, Anupriya; Gunasekaran, Manjula; S, Manivelan; Nainar, Palaniappan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:This study aims to determine the prevalence of antinuclear antibodies in pregnant women with bad obstetric history (BOH) against healthy multigravid women in and around Tirunelveli district Methods: This is a case-control study comprising 60 antenatal women with BOH against 60 multiparous pregnant women with no history of abortions. Antinuclear antibodies (ANA) were detected using indirect immunofluorescence with Hep-2 cell substrate, and enzyme-linked immunosorbent assay (ELISA). Results: Among BOH cases 19 (82.6%), 18 (78.26%) were positive by ELISA and indirect fluorescence antibody test (IFAT) method, respectively. Among controls, 4(17.39%) and 5(21.73%) individuals were positive by ELISA and IFAT methods, respectively. Of the 18 positives, homogenous pattern was most common followed by anticentromere pattern, fine speckled and coarse speckled pattern Conclusion: IFAT is considered to be gold standard in the diagnosis of autoimmune disorders, but ELISA appears to be a suitable simple alternative for testing rheumatological disorders.